Intrinsically Stretchable Electroluminescent Elastomers with Self‐Confinement Effect for Highly Efficient Non‐Blended Stretchable OLEDs - Li, Xiang‐Chun; Yao, Lanqian; Song, Wan; Liu, Fang; Wang, Qian; Chen, Jin; Xue, Qian; Lai, Wen‐Yong (Angewandte Chemie International Edition, 2023)
Ultra‐flexible stretchable organic light‐emitting diodes (OLEDs) are emerging as a basic component of flexible electronics and human‐machine interfaces. However, the brightness and efficiency of stretchable OLEDs remain still far inferior to their rigid counterparts, owing to the scarcity of satisfactory stretchable electroluminescent materials. Herein, we explore a general concept based on the self‐confinement effect to dramatically improve the stretchability of elastomers, without affecting electroluminescent properties. The balanced rigid/flexible chain dynamics under self‐confinement significantly reduces the modulus of the elastomers, resulting in the maximum strain reaching 806 %. Ultra‐flexible stretchable OLEDs have been constructed based on the resulting ISEEs, achieving unprecedented high‐performance non‐blended stretchable OLEDs. The results suggest an effective molecular design strategy for highly deformable stretchable displays and flexible electronics. Achieving high‐performance electroluminescence under large deformation remains a grand challenge. In this contribution, a general concept based on the self‐confinement effect has been proposed for the design and synthesis of non‐blended intrinsically stretchable electroluminescent elastomers (ISEEs). High‐performance non‐blended stretchable OLEDs have been constructed based on the resulting ISEEs.